Natural Resources Are Linked to Poverty and Industrialization - Ilya Zahra; Husain Muhal Tanjung (Penerbit Merdeka Kreasi, 2024)
This study examines the relationship between natural resources, poverty, and industrialisation in the context of economic development. Natural resources are often considered a key asset for development, but their suboptimal utilisation can exacerbate poverty and social inequality. This study analyses how the proper management of natural resources in industrialisation can be a driving force in eradicating poverty. Using theoretical approaches and case studies, it is found that natural resource-based industrialisation requires policies that support equitable distribution of output and environmental protection. The results show that synergies between wise use of natural resources, inclusive industrialisation policies, and poverty eradication strategies are essential to achieve sustainable development.